CLINICAL UTILITY OF SERUM LEVELS OF UBIQUITIN C-TERMINAL HYDROLASE AS A BIOMARKER FOR SEVERE TRAUMATIC BRAIN INJURY - Mondello, Stefania (2012)
BACKGROUND: Brain damage markers released in cerebrospinal fluid (CSF) and blood may provide valuable information about diagnosis and outcome prediction after traumatic brain injury (TBI). OBJECTIVE: This study examined concentrations of a novel brain injury biomarker Ubiquitin C-terminal Hydrolase-L1 (UCH-L1) in CSF and serum of severe TBI patients and their association with clinical characteristics and outcome. METHODS: This case-control study enrolled ninety-five severe TBI subjects (Glasgow Coma Score [GCS] ≤8). Using sensitive UCH-L1 sandwich ELISA, we studied the temporal profile of CSF and serum UCH-L1 levels over 7 days for severe TBI patients. RESULTS: Comparison of serum and CSF levels of UCH-L1 in TBI patients versus controls show robust and significant elevation of UCH-L1 in acute phase and over the 7 day study period. Serum and CSF UCH-L1 Receiver Operation Characteristics (ROC) curves further confirm strong specificity and selectivity for diagnosing severe TBI versus controls, with area under the curve (AUC) values in serum and CSF statistically significant at all time points up to 24 h (p < .001). The first 12 hour levels of both serum and CSF UCH-L1 in patients GCS 3–5 were also significantly higher than those with GCS 6–8. Furthermore, UCH-L1 levels in CSF and serum appear to distinguish severe TBI survivors versus non-survivors within the study, with non-survivors having significantly higher and more persistent levels of serum and CSF UCH-L1. Cumulative serum UCH-L1 level >5.22 ng/ml predicted death (odds ratio 4.8). CONCLUSION: Taken together, serum levels of UCH-L1 appear to have potential clinical utility in diagnosing TBI, including correlating to injury severity and survival outcome.